ANALISIS DAMPAK PENERAPAN GOOGLE CLASSROOM DALAM PEMBELAJARAN DARING SEMASA PANDEMI - Katmiasih Katmiasih; Muhammad Syahril Harahap; Sinar Depi Harahap (JURNAL MathEdu (Mathematic Education Journal), 2021)
The aim of this research is to know the impact of applying google classroom toward teachers and students SMK Negeri 1 Marancar online learning in pandemic period. The approach of the research used qualitative descriptive and triangulation was applied on data analysis technique which included interview, documentation, and questionnaire. Data sources were 2 teachers and 10 students. The result of the research shows the impact of online learning is positive impact which includes increase students and teachers ability of using ICT, shorter study time, learning can be done anywhere, and availability of adequate file storage space, and minimize of using paper. Furthermore, negative impact includes difficult to apply the right learning methods and media, learning materials are only in the form of documents, network interference, additional costs for buying internet quota, unfavorable class atmosphere, students become lazy to study, low student manners, teachers and students have to have adequate smartphone.